2020
DOI: 10.1099/jmm.0.001199
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa biofilm formation on endotracheal tubes requires multiple two-component systems

Abstract: Introduction. Indwelling medical devices such as endotracheal tubes (ETTs), urinary catheters, vascular access devices, tracheostomies and feeding tubes are often associated with hospital-acquired infections. Bacterial biofilm formed on the ETTs in intubated patients is a significant risk factor associated with ventilator-associated pneumonia. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 109 publications
2
24
0
Order By: Relevance
“…Similar to other prokaryotic TFs, both activating or repressing phenotypes could be observed upon manipulating TF binding in P. aeruginosa (73,(84)(85)(86)(87)(88)(89)(90)(91). However, we observed that most mutant strains did not show an overt biofilm-associated phenotype, even those of some previously known positive TFs such as RsaL (92), CprR (46), AlgB (76,93), CdpR (75), BqsR (Synonym: CarR) (71, 72) and PA3782 (63).…”
Section: Pa0225 Is a Novel Regulator Of Biofilm Productionmentioning
confidence: 56%
“…Similar to other prokaryotic TFs, both activating or repressing phenotypes could be observed upon manipulating TF binding in P. aeruginosa (73,(84)(85)(86)(87)(88)(89)(90)(91). However, we observed that most mutant strains did not show an overt biofilm-associated phenotype, even those of some previously known positive TFs such as RsaL (92), CprR (46), AlgB (76,93), CdpR (75), BqsR (Synonym: CarR) (71, 72) and PA3782 (63).…”
Section: Pa0225 Is a Novel Regulator Of Biofilm Productionmentioning
confidence: 56%
“…production , and which will be discussed more below. The additional three evolved mutations in separate genes that have all been linked to Pseudomonas biofilm production previously: mutant D acquired a mutation in the sensor histidine kinase rcsC 55 , M acquired a mutation in the type III secretion system gene pscQ 56 , and V acquired a mutation in the two component response regulator PA14_52250 57,58 (Table 2). While these are not the only mutations that distinguish the morphotypes from one another, these are leading candidates that could produce their varied biofilm phenotypes.…”
Section: High Diversity Is a Byproduct Of Clonal Interferencementioning
confidence: 99%
“…D acquired a mutation in the sensor histidine kinase rcsC (Nicastro et al 2009), M acquired a mutation in the type III secretion system gene pscQ (Wagner et al 2003), and V acquired a mutation in the two component response regulator PA14_52250 (Francis et al 2017;Badal et al. 2020) ( Table 2.…”
Section: High Diversity Is a Byproduct Of Clonal Interferencementioning
confidence: 99%
“…TCSs are numerous in P. aeruginosa, about twice as abundant as in the model organism Escherichia coli, and those that have been studied were found to be pivotal for orchestrating important cellular processes such as antibiotic resistance or the socalled acute-to-chronic lifestyle switch (Valentini and Filloux, 2016). Recently, several attempts at the global characterization of TCSs relied on phenotypic characterization of loss-of-function mutants (Badal et al;Gellatly et al, 2018;Kollaran et al, 2019;Wang et al, 2021a). However, while bringing new information on selected phenotypes, this approach does not globally address direct RR-target regulatory interactions.…”
Section: Introductionmentioning
confidence: 99%